Предмет: Математика,
автор: 23Julia10
Помогите решить.. 6 * (b - 3) = 10 - 2 * (b + 2) и 83 + 5 * (y - 3) = 3 * (8y - 9)
Ответы
Автор ответа:
0
6 * (b - 3) = 10 - 2 * (b + 2)
6b - 18 = 10 - 2b - 4
6b - 18 = 6 - 2b
6b + 2b = 6 + 18
8 b = 24
b = 3
83 + 5 * (y - 3) = 3 * (8y - 9)
83+5y-15=24y-27
83-15+27=24y-5y
95=19y
y=95 : 19
y=5
Похожие вопросы
Предмет: Биология,
автор: lizatymkiv99
Предмет: Математика,
автор: alinavalitiva
Предмет: Обществознание,
автор: Аноним
Предмет: История,
автор: Katushka01